Perception and its objects - Brewer, Bill, Dr. (Oxford : Oxford University Press, 2011)
Brewer presents and defends a new solution to a fundamental problem in the philosophy of perception. What is the correct theoretical conception of perceptual experience, and how should we best understand the most fundamental nature of our perceptual relation with the physical objects in the world around us?
Includes bibliographical references and index.
Keywords: Perception (Philosophy); Objectivity